2006
DOI: 10.1007/s10815-006-9069-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of persistent organochlorine contaminants in infertile patients from Tanzania and Germany

Abstract: The distribution of toxins between agricultural and industrial countries is different. Seminal plasma seems to be inert against chemicals. In patients with high serum concentrations of DDT and DDE pregnancy rates were impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…The study by Kalantzi et al (2009) (Erdmann et al, 1999). Levels of PCB congeners found in the current study are comparable to those measured in the general population in other non-industrialised developing countries such as Tanzania and India, but lower than those recently reported from Guinea-Bissau and from industrialised countries in the North (Anda et al, 2008;Linderholm et al, 2010;Todaka et al, 2010;Weiss et al, 2006). Interestingly, PCB levels in Brazilian delivering women were higher than those recently reported in the plasma of delivering women in South Africa and Vietnam Röllin et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
“…The study by Kalantzi et al (2009) (Erdmann et al, 1999). Levels of PCB congeners found in the current study are comparable to those measured in the general population in other non-industrialised developing countries such as Tanzania and India, but lower than those recently reported from Guinea-Bissau and from industrialised countries in the North (Anda et al, 2008;Linderholm et al, 2010;Todaka et al, 2010;Weiss et al, 2006). Interestingly, PCB levels in Brazilian delivering women were higher than those recently reported in the plasma of delivering women in South Africa and Vietnam Röllin et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
“…Magnusdottir et al (2005) concluded that poor semen quality is associated with sedentary work and obesity but not with plasma levels of fourteen organochlorine pesticides including DDT and metabolites. Weiss et al (2006) evaluating exposure, in Germany and in Tanzania, to a mixture of PCBs and pesticides, including DDT, found these pesticides had no impact on sperm quality. However high serum concentrations of DDT-DDE were associated with lower pregnancy rates in Germany.…”
Section: Studies With Little or No Evidence Of An Associationmentioning
confidence: 99%
“…In a study conducted on infertile couples in Germany and Tanzania organochlorine pesticides and PCBs were measured in serum, follicular fluid, or seminal plasma. For infertile men the semen parameters concentration, motility and morphology showed no correlation with serum PCB and PCB was found to have no impact on semen parameters (Weiss et al 2006). Rozati et al (2002) studied the determination of various PCB compounds in semen samples obtained from infertile and fertile individuals.…”
Section: Resultsmentioning
confidence: 99%